Frontispiece: Guest‐induced Assembly of Bis(thiosemicarbazonato) Zinc(II) Coordination Nanotubes. Issue 29 (5th July 2017) - Paterson, Brett M.; White, Keith F.; White, Jonathan M.; Abrahams, Brendan F.; Donnelly, Paul S.
Abstract : Reversible Sorption of CO 2 Templating molecules in square coordination nanotubes of dianionic bridging ligands and zinc(II) centers can be replaced by CO2 molecules as described by B. M. Paterson, B. F. Abrahams, P. S. Donnelly et al. in their Communication onpage 8370 ff.